SAT0330 Changes in lymphocytes and lymphocyte subsets in tofacitinib-treated patients with psoriatic arthritis. (12th June 2018) - Burmester, G.; Rigby, W.F.C.; Choy, E.; Nash, P.; Winthrop, K.; Mease, P.J.; Young, P.; Hendrikx, T.; Wang, C.; Menon, S.; Graham, D.
Abstract : Background: Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of psoriatic arthritis (PsA). Cytokines involved in lymphocyte development, function and homeostasis signal through JAKs, and reductions in mean lymphocyte count over time have been reported in tofacitinib-treated patients (pts) with rheumatoid arthritis. 1 Objectives: To characterise the effects of tofacitinib on absolute lymphocyte counts (ALCs) and lymphocyte subset counts (LSCs) in pts with PsA. Methods: Data were pooled from 2 placebo (PBO)-controlled, double-blind, Phase 3 studies (OPAL Broaden [12 months; NCT01877668 ]; OPAL Beyond [6 months; NCT01882439 ]). Pts had active PsA and inadequate response to ≥1 conventional synthetic DMARD (OPAL Broaden) or to ≥1 tumour necrosis factor inhibitor (OPAL Beyond). Pts were randomised to tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID, adalimumab 40 mg subcutaneous injection once every 2 weeks (active control; OPAL Broaden only) or PBO. PBO pts advanced in a blinded manner to tofacitinib 5 or 10 mg BID at Month (M)3. ALCs and LSCs were collected every 3 months as part of safety monitoring procedures in the Phase 3 studies (any abnormalities were confirmed upon retesting). Median ALCs and LSCs are reported up to M6. Incidence rates (pts with event/100 pt-years) for serious infections (SIs) were assessed by confirmed (two sequential measurements) ALC categories (≥2.0, <2.0–1.5, <1.5–1.0 and <1.0–0.5 × 10 3 /mm 3 ) up to M12. Results: The analysis included 816 pts: tofacitinib 5 mg BID, n=238; tofacitinib 10 mg BID, n=236; adalimumab, n=106; PBO, n=236. Up to M6, minimal decreases in median ALC were observed in pts who received tofacitinib 5 mg BID, tofacitinib 10 mg BID or PBO (up to M3 only) (Table). LSCs, including total T cells (CD3+), cytotoxic T cells (CD8+) and NK cells (CD16 +56+), showed a similar trend to ALC for both tofacitinib doses and PBO (Table), with minimal decreases over 6 months. B cells (CD19+) showed numerical increases across treatments. Percentage changes from baseline in LSCs at M6 showed a generally similar pattern to absolute values. In adalimumab-treated pts, ALCs and all LSCs increased over 6 months. Up to M6, no pts receiving tofacitinib or adalimumab had confirmed ALC<0.5×10 3 /mm 3 ; 1 pt receiving PBO had a confirmed ALC<0.5×10 3 /mm 3 over 3 months, resulting in discontinuation from the study before advancing to active treatment. Up to M12, SIs were reported in 7 tofacitinib- (including 2 pts who advanced from PBO) and 1 adalimumab-treated pt; of these, 1 SI (PBO advanced to tofacitinib) occurred >6 months after treatment initiation. There was no trend that suggested an increased risk of SIs in any ALC category (data not shown). Conclusions: Up to M6 in tofacitinib-treated pts with active PsA, minimal changes in ALCs and LSCs were observed. Although incidence of SIs did not appear to be related to ALC, conclusions are limited by the small number of events. Reference: [1] van Vollenhoven, et al. Ann Rheum Dis2016;75(suppl 2):258. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by A MacLachlan of CMC and funded by Pfizer Inc. Disclosure of Interest: G. Burmester Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, W. F. Rigby Consultant for: Roche, E. Choy Grant/research support from: BioCancer, Pfizer Inc, Roche, UCB, Consultant for: Amgen, Biogen, Chugai Pharma, Eli Lilly, Janssen, Novartis, Pfizer Inc, Regeneron, Roche, R-Pharm, Sanofi, Speakers bureau: Amgen, Bristol-Myers Squibb, Boehringer Ingelheim, Chugai Pharma, Eli Lilly, Hospira, MSD, Novartis, Pfizer Inc, Regeneron, Roche, Sanofi-Aventis, UCB, P. Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, K. Winthrop Grant/research support from: Bristol-Myers Squibb, Consultant for: AbbVie, Bristol-Myers Squibb, Galapagos, Eli Lilly, Pfizer Inc, UCB, P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer Inc, Sun, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer Inc, Sun, UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer Inc, UCB, P. Young Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc